Forest structure of Dalby Söderskog National Park - Achuthan, Kumetra (2021)
Carbon sequestration and storage is an ecosystem service supplied by forests, and is of increasing importance in the context of mitigation of global climate change. Forest pest invasions, driven primarily by globalizations, represent a risk to the efficiency of carbon sequestration as they may greatly reduce the amount of the living biomass in forests. This study provides a combined assessment of living trees and coarse woody debris in the temperate broadleaf forest of Dalby Söderskog National Park in southern Sweden. The specific objectives were: (1) to investigate the storage of biomass and carbon pools, in both live and dead wood; (2) to find out the relationship between the distribution of live and dead woody biomass and carbon in relation to stem diameter; (3) to analyse the relative share of live and dead wood carbon pools along the stem diameter gradient and (4) to study the effect of fungal tree diseases on biomass and carbon dynamics. Length and diameter of coarse woody debris including dead standing trees, cut stumps, and dead downed trees and branches were measured in 50 circular 100 m2 (5.64 m radius) sample plots. Data for living trees for the same sample plots were taken from a previous inventory. The results show that the studied broadleaf forest stored a total aboveground carbon stock of 176 t C/ha. Most carbon stock is stored by living trees (107.7 t C/ha), followed by downed deadwood (logs) (52.5 t C/ha) and standing dead wood (15.8 t/ha). The distribution of carbon storage in relation to stem diameter was species specific, and partly influenced by effects of Dutch elm disease and ash dieback. This study shows that old-growth forests store large carbon stocks in living and dead wood. In the specific case of Dalby Söderskog, effects of tree diseases in mean time have increased the relative share of dead wood compared to live tree volumes, in particular for smaller diameter trees. The mixed tree species composition of the forest has, however, buffered the effects of Dutch elm disease and ash dieback, and living tree biomass and carbon still remains considerably larger than the amounts stored in dead wood.